How Does Public External Debt Affect Corporate Borrowing Costs In Emerging Markets? - Celasun, Oya (IMF Working Papers; Working Paper ;, 2009)
Using data on syndicated loan issuances by emerging market firms, we find that an increase in the external debt of emerging market governments significantly raises the borrowing costs of the domestic corporate sector. This finding suggests that a higher level of public external debt "crowds out" foreign credit to the private sector by increasing the risk of a sovereign debt crisis and thereby making exposure to corporate sector debt less desirable. The effect is stronger in countries with weak creditor rights. The results highlight the potential costs of fiscal expansions for the domestic corporate sector even when debt is issued in foreign markets.